Child's Understanding of Cancer when Faced with Advancing Disease: A Retrospective Chart Review - Ghoshal, Arunangshu; Muckaden, Mary Ann; Garg, Chavi; Iyengar, Jayanthi; Damani, Anuja; Ganpathy, K.V. (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction It is difficult to comprehend a child's understanding of disease-related information as they might be unwilling to talk or feel inhibited about raising their concerns. Understanding children's perception is important to facilitate better communication in palliative care.Objectives To study child's understanding of advancing disease when referred to the Pediatric Palliative Care Services.Materials and Methods A retrospective chart review of 34 case record forms from March 2019 to March 2020 was conducted after obtaining a waiver of consent and Institutional Ethics Committee approval. The inclusion criteria were children having advanced cancer referred for palliative care, incomplete records were excluded. Data were analyzed using thematic analysis.Results Twenty-three were male, and 11 were female children, the mean age was 12 years. Five major themes were identified—the child's understanding of disease diagnosis and prognosis, nature of communication between parents and the child, barriers to communication, child's means of support, and interventions used during counseling.Conclusion Communication between children suffering from advanced cancer and their parents/caregivers is a sensitive issue, and noncommunication is often due to mutual effort to shield each other from the stress of difficult conversations. Lack of communication contributes to poor coping and forces children to seek comfort in other sources leaving parents distressed. Psychological interventions like resource building and psychoeducation are effective.
Keywords: cancer; palliative care; pediatrics; thematic analysis; qualitative research; chart review